Imaging protein–protein interactions in cell motility using fluorescence resonance energy transfer (FRET). (1st June 2004) - Parsons, M.; Vojnovic, B.; Ameer-Beg, S.
Abstract : Protein–protein interactions and signal transduction pathways have traditionally been analysed using biochemical techniques or standard microscopy. Although invaluable in the delineation of protein hierarchy, these methods do not provide information on the true spatial and temporal nature of complex formation within the intact cell. Recent advances in microscopy have allowed the development of new methods to analyse protein–protein interactions at very high resolution in both fixed and live cells. The present paper provides a brief overview of using fluorescence resonance energy transfer to analyse directly molecular interactions and conformational changes in various proteins involved in the regulation of cell adhesion and motility.